Antiepileptic drugs and suicide-related behavior: Is it the drug or comorbidity?. Issue 4 (August 2018) - Raju Sagiraju, Hari K.; Wang, Chen-Pin; Amuan, Megan E.; Van Cott, Anne C.; Altalib, Hamada H.; Pugh, Mary Jo V.
Abstract : Background: We sought to compare trends of suicide-related behavior (SRB) before and after initiation of antiepileptic drug (AED) therapy among AED users (with and without epilepsy) to that of individuals without AED use controlling for sociodemographic characteristics and mental health comorbidity. Methods: We used national Veterans Health Administration (VHA) data for post-9/11 veterans who received VHA care (2013–2014) without prior AED use. We conducted generalized estimation equation (GEE) analyses, stratified by epilepsy status and type of AED received, to assess the trend of SRB prevalence the year prior to and after the index date (date of first AED prescription/date of first health care encounter for non-AED users) controlling for sociodemographic factors and mental health comorbidity. Results: The GEE analysis showed significant curvilinear trends of SRB prevalence over the 24-month study period among the AED users, indicating that the probability of SRB diagnoses increased over time with a peak before the index month and decreased thereafter. Similar patterns were observed among non-AED users, but significantly lower odds for SRB. Among AED users, there were no significant differences by epilepsy status; however, higher SRB prevalence and differential SRB trajectory measures were observed among those who received AEDs with mood-stabilizing action. Conclusions: The peak of SRB prior to and rapid reduction in SRB after initiation of AED, and the finding that individuals eventually prescribed a mood-stabilizing AED (vs other AED or levetiracetam) had higher odds of SRB, suggests a strong possibility that the relationship of AED and SRB is one of residual confounding.